2012
DOI: 10.1001/archinternmed.2012.1159
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine Treatment of Subclinical Hypothyroidism, Fatal and Nonfatal Cardiovascular Events, and Mortality

Abstract: BACKGROUND Subclinical hypothyroidism (SCH) has been associated with ischemic heart disease (IHD); however, it is unknown whether treatment of SCH with levothyroxine sodium will reduce the risk of IHD. The aim of this study was to investigate the association between levothyroxine treatment of SCH with IHD morbidity and mortality. METHODS We used the United Kingdom General Practitioner Research Database to identify individuals with new SCH (serum thyrotropin levels of 5.01-10.0 mIU/L and normal free thyroxine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
160
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(188 citation statements)
references
References 30 publications
(42 reference statements)
7
160
0
18
Order By: Relevance
“…Data of the analysis of 55,000 CHD patients had shown a confidence interval of 1.89 (95% CI 1.28-2.80) for coronary heart disease events in TSH levels above 10 mIU / l [5] compared with euthyroidism and 1, 58 (95% CI 1.10-2.27) for fatal CHD. These risks did not increase in subjects with TSH lower than 7 mIU /L, the mortality from all causes not increased with an increase in TSH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data of the analysis of 55,000 CHD patients had shown a confidence interval of 1.89 (95% CI 1.28-2.80) for coronary heart disease events in TSH levels above 10 mIU / l [5] compared with euthyroidism and 1, 58 (95% CI 1.10-2.27) for fatal CHD. These risks did not increase in subjects with TSH lower than 7 mIU /L, the mortality from all causes not increased with an increase in TSH.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that according to prospective cohort studies an increase in the prevalence of MS components among adults with SH is observed [9], there is reason to assume potentiating influence on the formation of CVR both NAFLD and SH. The increasing of arteries intima-media thickness [6], predisposition to hypercoagulation, insulin resistance, oxidative stress [9] and endothelial dysfunction [5] also contributes to increase a CVR in SH. On the background of substitution therapy with Levothyroxine in patients with SH a decrease of carotid arteries intima-media thickness [6], an improvement of endothelial function [5], improvement of cardiac function [4] were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Лечебная тактика у больных с манифестным ги-потиреозом достаточно четко определена, в то вре-мя как целесообразность заместительной терапии СГ препаратами тиреоидных гормонов до сих пор остается предметом дискуссий [6][7][8][9][10]. Поскольку основной задачей, стоящей перед врачом, является предупреждение прогрессии субклинического в ма-нифестный гипотиреоз, то особенно актуальным является поиск немедикаментозных методов лече-ния данной патологии.…”
Section: Abstract: Subclinical Hypothyroidism Thyroid Gland Hypoxyunclassified
“…Helicobacter pylori infection, celiac disease). The principal adverse consequences of overtreatment are TSH suppression cardiovascular risk, skeletal or high risk of fracture, especially postmenopausal women, however, bone density does not reduce on short term administration and possible affective disturbances (Rees-Jones and Larsen, 1977;Razvi et al, 2012;Schneider et al, 2012;Ross, 1993;Biondi et al, 1994;Botella-Carretero et al, 2003).…”
Section: Introductionmentioning
confidence: 99%